STRATEGI KOMUNIKASI DINAS KESEHATAN KABUPATEN KEPULAUAN MERANTI DALAM PENCEGAHAN STUNTING DI KELURAHAN SELATPANJANG KOTA KECAMATAN TEBING TINGGI - Nisa Sabrina; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Stunting is a short toddler with chronic nutritional problems starting from the fetal condition, namely the age of 0-11 months and toddlers after 12-29 months, stunting will be visible when the baby is 2 years old or the First 1000 Days of Birth, so that the child looks short for his age. stunting can occur due to many factors, namely lack of maternal nutritional intake during pregnancy, lack of education, family economic problems, poor parenting and a less clean environment. The purpose of this study was to describe the Communication Strategy of the Meranti Islands Regency Health Office in preventing stunting in Selatpanjangan Kota Village, Tebing Tinggi Subdistrict and to find out the obstacles of the Communication Strategy of the Meranti Islands Regency Health Office in preventing stunting in Selatpanjang Kota Village, Tebing Tinggi Subdistrict. This research uses descriptive qualitative methods with data collection techniques in the form of interviews, observation and documentation. As for determining the research subject using Purposive techniques and Accindental techniques. informants in this study amounted to 7 people. While the data analysis technique uses interactive analysis according to Miles and Huberman, namely from collecting data, data reduction, data presentation and conclusion drawing. The data validity technique used in this research is the extension of participation and triangulation. The results of this study indicate that researchers used the strategic communication model from Iriantara, there are 5 elements, namely communicators with criteria, namely people who have high credibility, have attractiveness and power. The audience is all people in Selatpanjang Urban Village, especially pregnant women, nursing mothers, mothers of toddlers and adolescent girls, communication messages conveyed in the form of informative and persuasive. The media used are printed media, namely banners, leaflets and pamphlets, then social media used, namely Instagram @puskesmasselatpanjangkota, facebook Puskesmas Selatpanjang Kota, whatsapp group, namely the pregnant women class group (Kelas Bumil), and the website of the Selatpanjang City health center. There are 3 barriers to communication strategies, namely communicator barriers, media barriers and technological barriers. The results of this study can be a reference material for the Meranti Islands Regency Health Office regarding health communication strategies in the prevention of stunting as the next policy determinant and become information for the community about stunting.